2019
DOI: 10.1109/comst.2019.2932905
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Recent Advances in Transport Layer Protocols

Abstract: Over the years, the Internet has been enriched with new available communication technologies, for both fixed and mobile networks and devices, exhibiting an impressive growth in terms of performance, with steadily increasing available data rates. The Internet research community has kept trying to evolve the transport layer protocols to match the capabilities of modern networks, in order to fully reap the benefits of the new communication technologies. This paper surveys the main novelties related to transport p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 211 publications
(254 reference statements)
0
69
0
1
Order By: Relevance
“…TCP and all subsequent transport protocols that provide reliable end-to-end communication are based on end-to-end connections [54,64,80,83]. This has become a big problem for content-oriented Internet applications because connections are brittle, in most protocols the context exchange must be restarted if a connection is lost, a specific site must be selected to start the connection supporting content retrieval, and in-network caching cannot be used without compromising privacy.…”
Section: Reliable Transport Protocolsmentioning
confidence: 99%
“…TCP and all subsequent transport protocols that provide reliable end-to-end communication are based on end-to-end connections [54,64,80,83]. This has become a big problem for content-oriented Internet applications because connections are brittle, in most protocols the context exchange must be restarted if a connection is lost, a specific site must be selected to start the connection supporting content retrieval, and in-network caching cannot be used without compromising privacy.…”
Section: Reliable Transport Protocolsmentioning
confidence: 99%
“…Our results reveal the correlations between congestion packet losses and the cross-layer network metrics in detail. We believe these results have deep implications for all participants in the mobile Internet ecosystem (2) We model the rate allocation on wireless nodes as a utility maximization problem which yields optimal proportional fair data rates. The rates are then transformed into windows to control the TCP sending rates (3) We solve the congestion window regression problem by exploring the correlations between potential network metrics and the congestion windows.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 70.6% of data, the multimedia traffic, the virtual reality, and augmented reality data have stringent Quality of Service (QoS) constraints. It is apparent that today's prevalent congestion control algorithms, the TCP family, fall short of the critical performance requirement, especially on the last (wireless) hop [2][3][4][5][6][7][8]. In addition, current transport layer protocols are no longer suitable for the mmWave communication in 5G and Wi-Fi 6 [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrastructures, technologies and protocols that support communications over the Internet have significantly evolved over the years to support the needs of the connected society and the increase in mobile, desktop and machine-generated traffic [4]. In particular, the research community has recently shown a renewed interest in topics related to the transport layer, with novel transport protocols and extensions to TCP such as, e.g., Stream Control Transmission Protocol (SCTP), Quick UDP Internet Connections (QUIC), and Multi-path TCP (MPTCP) [14]. Furthermore, novel congestion control algorithms have also been proposed to address novel communication challenges, such as those introduced by new cellular Radio Access Networks (RANs) (e.g., 3GPP LTE, NR) [21].…”
Section: Introductionmentioning
confidence: 99%